PEGUKURAN MUTU LAYANAN PERUMAHAN KELAS MENENGAH BERBASIS KONSTRUKSI ECO-GREEN BUILDING: KAJIAN PERILAKU KONSUMEN - Suranto, Much; Sri Nugroho, Arif Julianto; Supratikno, Supratikno; Pratomo, Sigit Adhi; Santoso, Agus; Marjukah, Anis; Tasari, Tasari (Universitas Of Surakarta, 2023)
This study aimed to test the value of the gap as well as efforts to close the gap through the Servqual test. The population in this study were consumers of Kotabaru Land middle-upper housing through the Taman Anggrek Jogonalan Klaten brand where this housing has implemented the green building concept. Samples were taken in the research by purposive sampling as many as 40 respondents. Attributes in the green building service quality questionnaire include tangibles, reliability, responsiveness, assurance and empathy. Quantitative tests were carried out including item tests of reliability and validity and Servqual confirmation tests. The test results obtained that the confirmation value has a positive value of 58.27 with the lowest positive value on the reliability dimension. Improvement efforts must continue to be carried out by the company with the emphasis on improvement on the value that has the lowest positive dimension followed by the next positive value. The increasing service quality of the housing of Kotabaru Land-Taman Anggrek Klaten applying the green building concept will lead to the increasing of consumer satisfaction and strengthening of company competitiveness